1998
DOI: 10.1007/s002709900288
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided percutaneous angioplasty: Assessment of tracking safety, catheter handling and functionality

Abstract: The in vivo use of an MR-tracking PTA catheter is safe under most scanning conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 17 publications
2
56
0
1
Order By: Relevance
“…It also varies between different sequences and changes with the flip angle. Wildermuth et al [68] found sequences with higher duty cyles, as fast spin echo sequences, and high flip angles (90°) in gradient-recall echo sequences to cause most wire heating (18-20°C). However, studies using nitinol guidewires "off-label" did not show any harmful side effects caused by this heating in vivo, so its use is controversial [69].…”
Section: Safety Aspectsmentioning
confidence: 99%
“…It also varies between different sequences and changes with the flip angle. Wildermuth et al [68] found sequences with higher duty cyles, as fast spin echo sequences, and high flip angles (90°) in gradient-recall echo sequences to cause most wire heating (18-20°C). However, studies using nitinol guidewires "off-label" did not show any harmful side effects caused by this heating in vivo, so its use is controversial [69].…”
Section: Safety Aspectsmentioning
confidence: 99%
“…MRI-based active catheter tracking methods [44,45] may suffer from practical limitations, such as hampered mechanical properties as well as tissue heating caused by the catheter RF-coils [46,47]. Passive tracking methods based on susceptibility-artifacts induced by dysprosium oxide markers depict dis-crete points along the catheter only [48], and the use of catheter contrast agents with short T 1 relaxation times may suffer from insufficient signal difference between catheter and surrounding tissue [49].…”
Section: Catheter Tracking and Visualizationmentioning
confidence: 99%
“…Placing a catheter with attached RF coils within the body may also produce harmful heating effects if pulse sequences with high RF duty cycles are used (25). In a recent study, tissue heating was eliminated with the use of a wireless self-resonating RF circuit inductively coupled to the transmitting body coil and a receiving surface coil as an active catheter-tracking device (20).…”
mentioning
confidence: 99%